Mitochondrial targeting of mouse NQO1 and CYP1B1 proteins - Dong, Hongbin (2013)
Four dioxin-inducible enzymes—NAD(P)H:quinone oxidoreductase-1 (NQO1) and three cytochromes P450 (CYP1A1, CYP1A2 & CYP1B1)—are implicated in both detoxication and metabolic activation of various endobiotics and xenobiotics. NQO1 is generally regarded as a cytosolic enzyme; whereas CYP1 proteins are located primarily in endoplasmic reticulum (ER), CYP1A1 and CYP1A2 proteins are also targeted to mitochondria. This lab has generated Cyp1a1(mc/mc) and Cyp1a1(mtt/mtt) knock-in mouse lines in which CYP1A1 protein is targeted exclusively to ER (microsomes) and mitochondria, respectively. Comparing dioxin-treated Cyp1(+/+) wild-type, Cyp1a1(mc/mc), Cyp1a1(mtt/mtt), and Cyp1a1(−/−), Cyp1b1(−/−) and Nqo1(−/−) knockout mice, in the present study we show that [a] NQO1 protein locates to cytosol, ER and mitochondria, [b] CYP1B1 protein (similar to CYP1A1 and CYP1A2 proteins) traffics to mitochondria as well as ER, and [c] NQO1 and CYP1B1 targeting to mitochondrial or ER membranes is independent of CYP1A1 presence in that membrane.